2022
DOI: 10.1186/s13567-022-01098-x
|View full text |Cite
|
Sign up to set email alerts
|

Chicken miR-126-5p negatively regulates antiviral innate immunity by targeting TRAF3

Abstract: Innate immunity plays an essential role in preventing the invasion of pathogenic microorganisms. However, innate immunity is a double-edged sword, whose excessive activation is detrimental to immune homeostasis and even leads to a “cytokine storm” of the infected host. The host develops a series of negative regulatory mechanisms to balance the immune response. Here, we report a negative regulatory mechanism of chicken innate immunity mediated by miRNA. In the GEO database, we found that miR-126-5p was markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…miR-126 notably promoted NDV replication, suggesting that it regulates the host’s immune response by suppressing the ‘cytokine storm’ after viral infection. This negative regulation effectively prevents damage to the host caused by an excessive immune response [ 48 ]. Ishizaki et al have demonstrated that miR-126 regulates ERK signaling and cytokine production by directly targeting Spred1 (Sprouty-related Ena/VASP homology-1 domain-containing protein).…”
Section: Discussionmentioning
confidence: 99%
“…miR-126 notably promoted NDV replication, suggesting that it regulates the host’s immune response by suppressing the ‘cytokine storm’ after viral infection. This negative regulation effectively prevents damage to the host caused by an excessive immune response [ 48 ]. Ishizaki et al have demonstrated that miR-126 regulates ERK signaling and cytokine production by directly targeting Spred1 (Sprouty-related Ena/VASP homology-1 domain-containing protein).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that miRNAs are involved in the regulation of host cytokine storms upon pathogen invasion. MiR-223 attenuates acute inflammation in the lungs of mice caused by Streptococcus agalactiae [ 28 ]; inhibition of miRNA-34a promotes M2 macrophage polarization and ameliorates LPS-induced lung injury by targeting Kruppel-like factor 4 (KLF4) [ 29 ]; and miR-126-5p regulates host innate immune responses by suppressing the host inflammatory factor storm [ 30 ]. In the present study, we found that let-7d was able to suppress the MG-triggered cytokine storm to regulate the host immune response (Figure 1 E).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that DUSP10 (MKP5) inactivate cytokines and pro-inflammatory cytokines by inactivating MAP kinases to achieve equilibrium [ 39 , 41 ]. The other target gene, TRAF3 , encodes a protein that activates the secretion of type I IFNs, such as IFN-α and IFN-β [ 42 ]. After infection with the avian influenza virus, TRAF3 interacts with Mitochondrial antiviral signaling protein (MAVS), which is associated with retinoic acid-inducible gene I (RIG-I) signaling against virus infection [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%